D=\(\sqrt{2-\sqrt{3}}\) _ \(\sqrt{2+\sqrt{3}}\)
D=\(\frac{\sqrt{2}.\sqrt{2-\sqrt{3}}}{\sqrt{2}}\) _ \(\frac{\sqrt{2}.\sqrt{2+\sqrt{3}}}{\sqrt{2}}\)
D=\(\frac{\sqrt{4-2\sqrt{3}}}{\sqrt{2}}\) _ \(\frac{\sqrt{4+2\sqrt{3}}}{\sqrt{2}}\)
D=\(\frac{\sqrt{\left(\sqrt{3}\right)^2-\left(\sqrt{1}\right)^2}}{\sqrt{2}}\) _ \(\frac{\sqrt{\left(3\right)^2+\left(1\right)^2}}{\sqrt{2}}\)
D=\(\frac{\left|\sqrt{3}-1\right|}{\sqrt{2}}\) _ \(\frac{\left|\sqrt{3}+1\right|}{\sqrt{2}}\)
D=\(\frac{\sqrt{3}-1}{\sqrt{2}}\) _\(\frac{\sqrt{3}+1}{\sqrt{2}}\)
D=\(\frac{\sqrt{3}-1-\left(\sqrt{3}+1\right)}{\sqrt{2}}\)
D=\(\frac{\sqrt{3}-1-\sqrt{3}-1}{\sqrt{2}}\)
D=\(\frac{-2}{\sqrt{2}}\)
D=\(-\sqrt{2}\)
\(D=\sqrt{2-\sqrt{3}}-\sqrt{2+\sqrt{3}}\)
\(\Leftrightarrow\sqrt{2}D=\sqrt{4-2\sqrt{3}}-\sqrt{4+2\sqrt{3}}\)